Transformation of Shopping Culture from Local Market to Department Stores in Lalbandi, Sarlahi - Adhikari, Dharmendra (Janajyoti Journal, 2025)
This study explores the cultural transformation in consumer shopping behavior in Lalbandi, Sarlahi, Nepal, focusing on the transition from traditional local markets to modern departmental stores such as City Department Store, Dali Mart, and Landmark Department Store. The primary objective is to identify the key factors influencing this shift, including product pricing, consumer income, product variety, and perceptions of quality and convenience. A structured questionnaire was administered to 100 individuals, of which 84 valid responses were analyzed. Respondents were categorized into four age groups: 15–25, 25–35, 35–45, and above 45. The findings reveal a strong preference for departmental stores, especially among younger and middle-income consumers, driven by the availability of diverse products under one roof, improved service quality, and shopping convenience. The study highlights the growing impact of retail modernization in semi-urban Nepal and provides valuable insights for retailers, policymakers, and planners aiming to enhance customer satisfaction and adapt to changing consumer expectations.